Environmental factors contributing to stunting among under six years old children: a scoping review - Nazmeen Adline Fawwazah A. Fauzi; Idayu Badilla Idris; Zaleha Md Isa; Nur Fadhilah Mohd Razib (Universiti Kebangsaan Malaysia, 2025)
Stunting among young children is a serious public health issue worldwide. Stunting is also one of the major risk factors for poor physical and mental development of these children. It is known that children’s health and wellbeing are a result of exposure to unhealthy environment and a lack of stimulating activities especially in the low- and middle-income countries ultimately leading to the increase in the number of stunted children. This scoping review aims to identify environmental factors that contribute to stunting less than six years old children. In this review, PRISMA-ScR checklist to search Scopus, PubMed, and Web of Science databases. We included all original articles published between 2018 and 2022 and written in the English Language using combination of primary keyword (child*) and its MeSH and synonyms for population, and two secondary keywords (environ*) for exposure and (stunt*) for outcome as searching strategy. By using PRISMA extension for scoping reviews, 65 articles were reviewed and finally 25 eligible studies were included. The included studies showed that lack of clean water access, poor sanitation, and poor hygiene practice were associated with higher risk of stunting among these children. Improper solid waste management, area of residence and type of housing, poor quality of cooking fuels and poor air quality, presence of intestinal parasitic infection and increased blood lead levels, were also noted as potential environmental factors that affect stunting. Investment in infrastructure to provide safe and clean water and adequate sanitation facilities in communities with expanded health promotion activities focusing on hygiene practices and waste management may thus stunting and improve children’s health outcome.